A randomised trial of self-management planning for adult patients admitted to hospital with acute asthma. - Osman, L; Calder, C; Godden, D; Friend, J; McKenzie, L; Legge, J; Douglas, J (2002)
BACKGROUND: There is still debate over the benefit of self-management programmes for adults with asthma. A brief self-management programme given during a hospital admission for acute asthma was tested to determine whether it would reduce readmission. METHOD: A randomised controlled trial was performed in 280 adult patients with acute asthma admitted over 29 months. Patients on the self-management programme (SMP) received 40-60 minutes of education supporting a written self-management plan. Control patients received standard care (SC). RESULTS: One month after discharge SMP patients were more likely than SC patients to report no daytime wheeze (OR 2.6, 95% CI 1.5 to 5.3), no night disturbance (OR 2.0, 95% CI 1.2 to 3.5), and no activity limitation (OR 1.5, 95% CI 0.9 to 2.7). Over 12 months 17% of SMP patients were re-admitted compared with 27% of SC patients (OR 0.5, 95% CI 0.3 to 1.0). Among first admission patients, OR readmission (SMP v SC) was 0.2 (95% CI 0.1 to 0.7), p<0.01. For patients with a previous admission, OR readmission was 0.8 (95% CI 0.4 to 1.6), p=0.6. SMP patients were more likely than SC patients to be prescribed inhaled steroids at discharge (99% v 92%, p=0.03), oral steroids (98% v 90%, p=0.06), and to have hospital follow up (98% v 84%, p<0.01) but adjustment for these differences did not diminish the effect of the self-management programme. CONCLUSIONS: A brief self-management programme during hospital admission reduced post discharge morbidity and readmission for adult asthma patients. The benefit of the programme may have been greater for patients admitted for the first time. The programme also had a small but significant effect on medical management at discharge.